Effectiveness of Metformin on Weight Loss in Non-Diabetic Individuals with Obesity - Seifarth, C.; Schehler, B.; Schneider, H. J. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The efficacy of metformin for the treatment of obesity has been evaluated in few clinical trials with inconclusive results. Moreover, the effectiveness in a real-life outpatient setting has not been tested until today. In this study we aimed to examine the effectiveness of metformin as a weight reducing drug in obese and overweight patients with regard to their degree of insulin resistance.We treated 154 consecutive patients with a body mass index ≥27 kg/m2 in an outpatient setting over 6 months with metformin up to a dosage of 2 500 mg per day. Additionally, we included 45 untreated patients as controls. Patients were monitored for weight changes over 6 months. Before metformin treatment was started insulin sensitivity was determined in all patients by calculating HOMA index and Matsuda index after a 75 g oral glucose tolerance test.The mean weight loss in the metformin treated group was 5.8±7.0 kg (5.6±6.5%). Untreated controls gained 0.8±3.5 kg (0.8±3.7%) on average. Patients with severe insulin resistance lost significantly more weight as compared to insulin sensitive patients. The percentage of weight loss was independent of age, sex or BMI.Metformin is an effective drug to reduce weight in a naturalistic outpatient setting in insulin sensitive and insulin resistant overweight and obese patients.
Keywords: metformin; obesity; insulin resistance